"A-PePSI LIGhT" Assessment Score to Predict Pressure Sore Impaired Healing Late Recurrence, Immobility, Greater Surface, Inhibited Thrombocytes. Issue 2 (February 2022) - Anker, Alexandra M.; Ruewe, Marc; Prantl, Lukas; Geis, Sebastian; Kehrer, Andreas; Baringer, Magnus; Schiltz, Daniel; Zeman, Florian; Vykoukal, Jody; Klein, Silvan M.
Abstract : Background: Complication rates of up to 46 percent are reported following pressure sore surgery. Pressure sore patients often exhibit ineffective postoperative wound healing despite tension-free flap coverage, necessitating surgical revision and prolonged hospitalization. Rather than pressure sore recurrence, such impaired healing reflects a failed progress through the physiologic stages of the normal wound-healing cascade. The principal objective of the study reported here was to elucidate potentially modifiable inherent variables that predict predisposition to impaired healing and to provide a tool for identifying cases at risk for complicated early postoperative recovery following pressure sore reconstruction. Methods: A retrospective chart review of late-stage (stage 3 or higher) sacral and ischial pressure sore patients who underwent flap reconstruction from 2014 to 2019 was performed. A multivariable logistic regression model was used to identify key patient and operative factors predictive of impaired healing. Furthermore, the Assessment Score to Predict Pressure Sore Impaired Healing (A-PePSI) was established based on the identified risk factors. Results: In a cohort of 121 patients, 36 percent exhibited impaired healing. Of these, 34 patients suffered from dehiscences, necessitating surgical revision. Statistically significant risk factors comprising late recurrence (OR, 3.8), immobility (OR, 12.4), greater surface (>5 cm diameter; OR, 7.3), and inhibited thrombocytes (aspirin monotherapy; OR, 5.7) were combined to formulate a prognostic scoring system (A-PePSI LIGhT). Conclusions: The A-PePSI LIGhT score serves as a prognostic instrument for assessing individual risk for impaired healing in pressure sore patients. Preoperative risk stratification supports rational decision-making regarding operative candidacy, allows evidence-based patient counseling, and supports the implementation of individualized treatment protocols. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.